Design, Optimization, and in vitro Evaluation of Orally Disintegrating Tablets Containing Amlodipine Besylate - Şahbaz, Sevinç; Özer-Önder, Setenay; Uğurlu, Timuçin (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: In this study, it was aimed to prepare orally disintegrating tablet formulations of amlodipine besylate by applying the experimental design. Materials and Methods: A face-centered, central composite 32 full factorial design was applied to evaluate the effects of filler ratio (MAN: MCC; X1) and super disintegrant percentage (SSG; X2) on the critical tablet characteristics such as tensile strength (Y1), disintegration time (Y2) and dissolution rate (5th min) (Y3). Results: The Quadratic model showed good predictability (p<0.0001) on tablet tensile strength and the linear model was found to be suitable for disintegration time and dissolution time profiles (p<0.001 and p>0.05 respectively). In addition to the compendial quality control tests for tablet formulations, a texture analyzer with the tablet disintegration rig fixture was also used for the disintegration test and onset of disintegration (s), end of disintegration (s), disintegration rate (mm/s), duration of swelling (s), swelling distance (mm), residual height (mm) values were obtained. Conclusion: It was determined that F9, with the highest MAN: MCC (75:25) and SSG (10%) ratios, met all pharmacopeia standards and gave the best disintegration time results (18.55±1.28 s), which is a very crucial factor for orally disintegrating tablet characterization, compared to other formulations.
Keywords: Amlodipine besylate; Design of experiments; Texture analyzer; Orally disintegrating tablet; Direct compression tableting